Stem Cells and Translational Medicine: From Research to Clinical Procedures - Del Fante, Claudia; Monti, Manuela; Alberto Redi, Carlo; Cervio, Marila; Scudeller, Luigia; Rodriguezy Baena, Ruggero; Perotti, Cesare (Current Tissue Engineering (Discontinued), 2015)
Mesenchymal stem cells (MSCs) are multipotent adult stem cells with unique biological properties, typically associated with their mesodermal lineage. Various in vitro studies and preclinical animal model showed that MSCs are promising for cell therapy showing the ability to home to sites of inflammation after tissue injury, to differentiate into various cell types and secrete multiple bioactive molecules capable of stimulating recovery of injured cells by inhibiting inflammation (known as paracrine effect). MSCs also show the lack of immunogenicity and have the ability to perform immunomodulatory functions. Undoubtedly the use of MSCs either taking advantage of their immunomodulatory properties or their ability to repair, with different cooperative mechanisms, an injured tissue will represent the standard therapy in the near future. However, there is a lack of consensus on several issues that need to be addressed: a better understanding of the MSCs mechanism of action, type of cells and sources, optimal cell dose and route of administration together with standardized Good Manufacturing Practice procedures and strict surveillance of genetic instability after multiple passages in culture. This concise review is not meant to be exhaustive on all diseases and conditions currently treated with MSCs, but only focuses on some pathologies (ischemic cardiovascular diseases, critical limb ischemia, bone and cartilage regeneration, neural diseases) at high socio-economic impact, that historically have been under investigation for regenerative purposes.
Keywords: stem cells